2015
DOI: 10.1016/j.cell.2015.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Rod-Derived Cone Viability Factor Promotes Cone Survival by Stimulating Aerobic Glycolysis

Abstract: Rod-derived cone viability factor (RdCVF) is an inactive thioredoxin secreted by rod photoreceptors that protects cones from degeneration. Because the secondary loss of cones in retinitis pigmentosa (RP) leads to blindness, the administration of RdCVF is a promising therapy for this untreatable neurodegenerative disease. Here, we investigated the mechanism underlying the protective role of RdCVF in RP. We show that RdCVF acts through binding to Basigin-1 (BSG1), a transmembrane protein expressed specifically b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
390
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 353 publications
(409 citation statements)
references
References 67 publications
13
390
0
6
Order By: Relevance
“…protection via activity of rod-derived cone viability factor (30). Notably, ATG5 expression did not vary between control and experimental mice.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…protection via activity of rod-derived cone viability factor (30). Notably, ATG5 expression did not vary between control and experimental mice.…”
Section: Discussionmentioning
confidence: 84%
“…Notably, we demonstrate that enhancing the mTOR pathway in rods can also promote cone cell survival. This may be due to rod-derived nutritional factors that are required to sustain cones, and thus, promoting rod survival may enhance the release of such factors and concurrently increase preservation of cones (30)(31)(32). In a study of rod-cone dystrophy, heightened rodderived cone viability factor (RdCVF) expression led to cone preservation for up to 5 weeks (33).…”
Section: Discussionmentioning
confidence: 99%
“…While basigin‐1 transcript (NM_001728), with a third immunoglobulin domain (Ig0), is only expressed specifically in the retinal photoreceptors 19, 26, 27. Basigin‐1, associating with a protein secreted from rods, being named as rod‐derived cone viability factor (RdCVF) and glucose transporter (Glut)‐1, form a complex at the cone surface to increase glucose uptake and promotes cone survival 28, 29. Consistent with the tissue specificity of basigin‐1, our results have shown that microglia BV2 cells selectively express basigin‐2.…”
Section: Discussionmentioning
confidence: 99%
“…Contrairement aux mammifères, chez lesquels les bâtonnets dominent du fait des moeurs nocturnes de leurs ancêtres, les oiseaux descendant des dinosaures ont une vision diurne et une majorité de photorécepteurs à cônes. Cet artifice biologique a grandement facilité l'identification par spectrométrie de masse d'une protéine, basigin-1 (BSG1), possédant un seul domaine transmembranaire interagissant avec RdCVF à la surface des cônes [5]. BSG1 est un épissage alternatif du gène BSG, spéci-fiquement exprimé par les photorécep-teurs, qui possède un domaine extracellulaire additionnel impliqué dans sa liaison avec RdCVF [6].…”
unclassified
“…une matrice d'électrodes à la surface de la rétine pour stimuler les cellules restantes après la disparition des photorécepteurs [2][3][4]. À l'heure actuelle, deux de ces dispositifs ont obtenu l'autorisation de mise sur le marché en démontrant qu'ils restituent aux patients aveugles (ayant perdu la vue parfois depuis plusieurs années) la capacité de retrouver des fonctions visuelles allant de la simple perception de flashs (phosphènes) jusqu'à la lecture [5,6]. Ces résultats très encourageants ne permettent cependant pas aux patients de retrouver leur autonomie et le réel bénéfice de ces prothèses est, à l'heure actuelle, encore limité.…”
unclassified